Defining authorship, debating authenticity: problems of authority from classical antiquity to the Renaissance - Berardi, Roberta; Filosa, Martina; Massimo, Davide (Beiträge Zur Altertumskunde Series, 2020)
The volumes published in the series Beiträge zur Altertumskunde comprise monographs, collective volumes, editions, translations and commentaries on various topics from the fields of Greek and Latin Philology, Ancient History, Archeology, Ancient Philosophy as well as Classical Reception Studies. The series thus offers indispensable research tools for a wide range of disciplines related to Ancient Studies.